2020
DOI: 10.1093/ageing/afaa246
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood walkability and physical activity: moderating role of a physical activity intervention in overweight and obese older adults with metabolic syndrome

Abstract: Background While urban built environments might promote active ageing, an infrequently studied question is how the neighbourhood walkability modulates physical activity changes during a physical activity intervention programme in older adults. We assessed the influence of objectively assessed neighbourhood walkability on the change in physical activity during the intervention programme used in the ongoing PREvención con DIeta MEDiterránea (PREDIMED)-Plus trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Studies were published between 2009 and 2021 (Table 2). Most studies (n = 16) recruited samples from populations with a known health risk, including metabolic disorders (e.g., diabetes risk, metabolic syndrome) [32,35], coronary heart disease risk factors [42], overweight or obesity [36], history of cancer [40], high blood pressure [51], and sedentary behaviour or physical inactivity [34,43,44,46,48] or a combination of risk factors [33,37,39]. Six studies included samples from general (non-clinical) populations [38,41,45,47,49,50].…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were published between 2009 and 2021 (Table 2). Most studies (n = 16) recruited samples from populations with a known health risk, including metabolic disorders (e.g., diabetes risk, metabolic syndrome) [32,35], coronary heart disease risk factors [42], overweight or obesity [36], history of cancer [40], high blood pressure [51], and sedentary behaviour or physical inactivity [34,43,44,46,48] or a combination of risk factors [33,37,39]. Six studies included samples from general (non-clinical) populations [38,41,45,47,49,50].…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
“…Several studies recruited participants from specific demographically-defined subpopulations such as African American, Hispanic or Latino [38,44], low socioeconomic position [34,47,48], and males [40] or females only [38,39,44]. The target age of participants varied with some studies sampling older adults only [33,37,41,47], and the remainder including samples representative of multiple age groups (e.g., young, middle-aged, and older adults). Three studies recruited some [32] or all [39,51] participants from rural areas while all other studies recruited participants from urban areas.…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
“…The environment appears to play a more important role in the decline in functioning associated with aging; however, older adults have been the least studied age group, with inconsistent results ( 38 , 39 ). Colom et al ( 16 ) and King et al ( 12 ) discovered that older adults who lived in more walkable neighborhoods had higher levels of physical activity and a lower BMI. However, Berke et al ( 40 ) discovered that low BMI levels were not found in higher walkability neighborhoods, particularly for men.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars recently advocated further research into the specific mechanisms of the linkage between the built environment and obesity ( 29 , 42 ), as the built environment may work to influence overweight through mediators such as different levels of physical activity, travel mode, sedentary behavior, and social capital ( 16 , 21 , 26 , 43 ). According to Poortinga ( 44 ), the majority of the mediations of PA on neighborhood environment and obesity are limited, implying that there are other unobserved mediating variables that negatively affect health outcomes in highly walkable neighborhoods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation